Gesture Signs Representing Emotions in the Animated Movie Inside Out 2: A Semiotic Study - Dewi, Alya Putri; Haq, Muhammad Syafiqul; Prasodjo, Ryu Omar Shadiq; Rahmah, Shindy Aulia (Universitas Pamulang, 2026)
This study investigates how Inside Out 2 (2024) employs gesture signs to convey emotional meaning through its animated characters. Guided by Charles Sanders Peirce’s semiotic framework; icon, index, and symbol. The analysis focuses on how body movements, posture, and facial expressions reveal the psychological conditions of each emotion. Using a qualitative descriptive method, the research identifies and examines selected scenes that prominently display meaningful gestures, including moments where nonverbal cues take precedence over spoken dialogue. The findings show that each emotion consistently uses specific gesture patterns to communicate internal states: icons reflect natural human reactions, indexes point to immediate bodily or psychological responses, and symbols rely on culturally shared knowledge to express more abstract emotional ideas. These gestures not only enrich the visual appeal of the movie but also function as deliberate semiotic tools that guide the audience’s interpretation of shifting emotional dynamics. The study further highlights that gesture meaning becomes more powerful when multiple sign types appear simultaneously, for instance, when facial tension, hand movements, and bodily stance work together to signal complex or layered feelings. Overall, the research demonstrates that animated gestures in Inside Out 2 serve as essential elements in multimodal storytelling, offering insight into how nonverbal signs help viewers understand emotional processes and engage more deeply with character development.